What drives the dehumanization of consensual non-monogamous partners? - Rodrigues, D. L. (2021)
We built upon a recent study by Rodrigues et al. (2018) by investigating potential mechanisms driving the dehumanization of consensual non-monogamous (CNM) partners. Using a between-subjects experimental design, we asked 202 Portuguese individuals (158 women; Mage = 29.17, SD = 9.97) to read the description of two partners in either a monogamous, open, or polyamorous relationship, and to make a series of judgments about both partners. Results showed the expected dehumanization effect, such that both groups of CNM partners (open and polyamorous) were attributed more primary (vs. secondary) emotions, whereas the reverse was true for monogamous partners. Moreover, results showed that the dehumanization effect was driven by the perception of CNM partners as less moral and less committed to their relationship. However, these findings were observed only for individuals with unfavorable (vs. favorable) attitudes toward CNM relationship. Overall, this study replicated the original findings and extended our understanding of why people in CNM relationships are stigmatized.